Mechanisms of action for empirically supported interventions to reduce adolescent sexual risk behavior: A randomized controlled trial - Gibson, Laurel P. (J Adolesc Health, 2020)
PURPOSE: Adolescents are at high risk for sexually transmitted infections including HIV. Interventions to reduce adolescent sexual risk often have modest outcomes. Understanding of the mechanisms of program effectiveness is needed in order to develop stronger interventions. We utilized a randomized controlled trial (RCT) to examine mechanisms of response to two empirically supported interventions: motivational interviewing (MI) versus behavioral skills training (BST). METHODS: 262 adolescents (M age = 15.89, SD = 1.24, 34% female, 61% Latinx) were recruited from juvenile justice programs in the United States; all youth were randomized to MI or BST. Primary outcomes included 1) theory-based mechanisms: condom use attitudes, norms, self-efficacy, and intentions measured before and immediately after the interventions and 2) risky sexual behavior (frequency of unprotected sex) and condom use measured three months post-intervention. RESULTS: Both interventions significantly increased positive attitudes towards condom use, self-efficacy for condom use, and intentions to use condoms posttest, with no differences by condition. Neither intervention impacted norms for condom use. Both interventions significantly decreased risky sexual behavior and increased condom use at the 3-month follow-up. The pattern of associations of TPB constructs to behavior were of similar magnitude in the two groups. CONCLUSIONS: Results indicate common mechanisms of action for these two interventions and support use of transdiagnostic mechanisms of treatment impact for sexual risk reduction.